Mini Box Theater: Development and Validation of an Innovative Storytelling Media for Children Aged 5-6 Years - Sedana Suci, I Gede; Marsono; Suyanta, I Wayan; Sindu Putra, Ida Bagus Komang; Kamalia Jaya, Praptika; Eka Suciari Putri, Ida Ayu (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This research focuses on developing and validating the Mini Box Theater as an innovative storytelling medium for children aged 5-6 years at Bali Kumara Batubulan Kindergarten. The study followed the Research and Development (R&D) methodology, utilising the ADDIE and Dick and Carey models. The objectives were to design, develop, and assess the feasibility of the Mini Box Theater for enhancing storytelling activities. Data were collected through observations, teacher interviews, and expert validation from five validators specialising in early childhood education and media development. Content validation involved evaluating storytelling components such as literacy, children’s ability to express feelings, and participation in pre-reading activities. Media validation focused on technical aspects like design, material suitability, and ease of use. The results demonstrated high content validity, with a Content Validity Ratio (CVR) 1 for all items. Based on expert feedback, revisions were made to improve the media’s visual appeal and enhance character interactions. Limitations of the study included the absence of comprehensive field testing due to time constraints. Despite this, the Mini Box Theater shows promise for improving children’s storytelling skills, vocabulary, and cultural awareness. Future research should focus on field testing to assess the media’s effectiveness in real classroom settings and explore its potential for broader educational applications. This study contributes to early childhood education by offering a culturally relevant and engaging tool for language development.